More Than Mindfulness: Why Self-Efficacy Still Matters Most in Inclusive Teaching Stress - Risnawati, Erna (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2025)
High levels of occupational stress among teachers in inclusive classrooms particularly those educating children with special needs (CWSN), remain a pressing concern in Indonesia. The lack of specialized training and increasing classroom demands exacerbate the psychological burden on inclusive educators. This study aims to examine the relationship between self-efficacy, mindfulness, and teacher stress, and to explore whether mindfulness moderates the relationship between self-efficacy and stress. Adopting a quantitative correlational design, this study involved 100 special education teachers from inclusive schools selected through purposive sampling. Instruments used include the Teacher Stress Inventory, all of which demonstrated strong validity and reliability. Correlation analyses revealed that self-efficacy was significantly and negatively associated with teacher stress, while mindfulness showed no direct association with stress. However, a positive correlation was found between social self-efficacy and mindfulness. Moderation analysis indicated that mindfulness did not significantly moderate the relationship between self-efficacy and stress. This study contributes to the literature by integrating mindfulness and self-efficacy in the context of Indonesian inclusive education, a population often underrepresented in existing research. The findings highlight the importance of institutional support and structured mindfulness programs to strengthen teachers’ self-efficacy and alleviate stress in inclusive educational settings.